ZERO DEBT STRATEGY FOR EDUCATIONAL INSTITUTION SUSTAINABILITY: REVIEW OF MUDHARABAH CONTRACTS IN BUSINESS UNIT DEVELOPMENT - Dewi, Ratna; Iqbal, Muhammad; Fathony, Aditya Achmad; Rahayu, Nenden Sri; Setiawan, Djodi (FEBI UIN Sunan Gunung Djati Bandung, 2025)
This study explores the integration of Mudharabah contracts as a financial strategy for private educational institutions to achieve sustainability without relying on debt. Private schools face significant challenges due to limited funding sources and dependency on tuition fees, which often lead to financial strain. The research highlights the potential of Mudharabah-based business units in creating alternative revenue streams to reduce financial burdens and enhance stability. By adhering to Sharia principles, such as profit-sharing agreements and transparent management, educational institutions can foster ethical, debt-free growth. This qualitative study employs content analysis to examine the literature on Mudharabah practices and their role in improving financial resilience. The findings underscore the importance of diversifying income through Sharia-compliant business models to ensure long-term financial independence and quality education delivery.